2005
DOI: 10.1002/marc.200590027
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover: Macromol. Rapid Commun. 14/2005

Abstract: Front Cover: Carbon spheres were covalently functionalized with polymers by using an in situ atom transfer radical polymerization approach, resulting in significantly improved dispersibility in organic solvents. SEM and TEM observations show a uniform distribution of the carbon spheres in the continuous polymer phase. Further details can be found in the Communication by Y. Z. Jin, C. Gao,* H. W. Kroto, and T. Maekawa on page 1133.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The results indicated that there were ≈3.4 initiator moieties per 1000 carbons or 0.268 mmol per gram of AC attached to the AC surface. This result was similar to that of carbon spheres and lower than that of carbon nanotubes 22, 31, 32. The decomposition temperature was increased to ≈350 °C after the SI‐AGET ATRP of MMA.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…The results indicated that there were ≈3.4 initiator moieties per 1000 carbons or 0.268 mmol per gram of AC attached to the AC surface. This result was similar to that of carbon spheres and lower than that of carbon nanotubes 22, 31, 32. The decomposition temperature was increased to ≈350 °C after the SI‐AGET ATRP of MMA.…”
Section: Resultssupporting
confidence: 67%
“…The difference in weight loss between AC@OFG and AC@Br was 4%, consistent with the attachment of 2‐methylpropionyl bromide groups on the AC surface, as shown in Scheme . The results indicated that physically or noncovalently attached chemicals could be removed from the resulting product by careful washing 22. Thus, the initiator concentration could be calculated from the 4% weight loss difference before and after introduction of the initiator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon materials include carbon nanotubes, carbon sphere, carbon black, and carbon fibers, and have being extensively applied to many fields. To broaden their ranges of applications, the method of grafting polymers onto their surfaces1–3 is adopted. Carbon black is used widely as pigment in the coating4 and ink5 industry, and as reinforcing agent in the rubber industry,6 because it has excellent properties, such as chemical, heat resistance, and electroconductivity, etc.…”
Section: Introductionmentioning
confidence: 99%